Nurturing transformative participation: A participatory realist review of mental health interventions in low resource settings - Rochelle A. Burgess; Hannah Maria Jennings; Kaaren Mathias; Farirai Gumbonzvanda; Nyaradzayi Gumbonzvanda; Garima Gupta; Cheyann Heap; Sumeet Jain; Pashupati Mahat; Rakchhya Maharjan; Sujen Man Maharjan; Pooja Pillai; et al. (SSM - Mental Health)
Purpose: The importance of involving people with lived experiences of mental health difficulties and the communities they inhabit, in interventions for them is now widely recognised. However, there is a lack of scrutiny around the theory and practice of how - and to what extent - participation occurs in global mental health interventions. The aim of this review was to examine existing literature and consult with community groups in low and middle income settings in order to understand how, for whom and under what conditions participatory approaches work to lead to positive outcomes for mental health. Methods: Informed by a realist approach, we developed a new methodology combining a realist literature synthesis with the experiences of everyday citizens and service users from communities within low and middle income countries. Across a ten-step process we systematically reviewed literature and iteratively conducted focus group discussions, to inform the development of mid-range theories and a programme theory of participation that was reviewed and approved by community members in our LMIC sites. Results: Participation in global mental health varies widely across contexts and programmes. We developed a programme theory based on seven principles, to understand how and under what circumstances participation can be meaningful, transformative and lead to improved mental health. The principles were: 1. Interventions and programmes should be built on strong relationships with communities in their localities; 2. Long term engagement in a locality means that services are more responsive; 3. A trusting, supportive and collaborative therapeutic relationship is critical when responding to mental health needs; 4. it is important to integrate existing beliefs, metaphors and traditions into understandings about mental health; 5. Groups and peer support can be important sources of social support leading to changes at individual and group levels; 6. Providing mental health support in spaces which are physically and emotionally safe helps marginalised groups to participate; and 7. Facilitating opportunities for participation and collective action strengthens mental health and social wellbeing. Conclusions: Bringing together theory and practice, this realist review underscores the importance of meaningful participation in global mental health. Through this work we develop a programme theory, identifying seven key principles important to facilitating transformative participation.